An Analysis on Anti-Islamic Movements in Europe From 11 September to Present: The Case of Sweden - Kişi, Erden (Fırat University, 2024)
In every period of history, it has been observed that there is prejudice against different ethnic and religious groups in all world societies. In some periods, these prejudices have caused great suffering in human history. It was observed that, especially after the French Revolution, with the nationalism movement that started to rise in Europe, the prejudices of the European people against other world rights quickly turned into racism. Later, it was seen that Western societies harbored the harshest prejudices against Islamic societies. Of course, the historical heritage of societies has a great impact on the formation of this situation. Especially in the periods when Western societies acted with a Crusader mentality, Islam literally became an "other" of the West. Ultimately, in this study; An analysis has been made on where anti-Islamism, which has been on the rise in Europe since the events of September 11, has come from and the direction it will develop. Especially the political and theological dimensions of the recent events in Sweden have been tried to be understood. As a result of the subsequent developments, the effects of the rising anti-Islamism in Europe on Islamic societies were analyzed. Finally, the political, sociological and theological steps necessary to overcome the problem are mentioned. During the study process, a scientific method was followed by scanning the literature.

Tarihin her döneminde tüm dünya toplumlarında farklı etnik ve dini gruplara karşı bir ön yargının olduğu görülmüştür. Kimi dönemlerde ise bu önyargılar, insanlık tarihi adına büyük acıların yaşanmasına neden olmuştur. Özellikle Fransız İhtilali sonrasında, Avrupa’da yükselmeye başlayan milliyetçilik akımı ile beraber Avrupa halklarının diğer dünya haklarına karşı sahip olduğu ön yargıların, kısa süre içerinde ırkçılığa dönüştüğü gözlenmiştir. Daha sonrasında ise Batılı toplumların en katı ön yargıları ise İslam toplumlarına karşı beslediği görülmüştür. Bu durumun oluşmasında pek tabii ki toplumların sahip olduğu tarihi mirasın, büyük bir etkisi bulunmaktadır. Özellikle Batılı toplumların Haçlı zihniyeti ile hareket ettiği dönemlerde İslam, tam anlamı ile Batı’nın bir ‘‘öteki’’si olmuştur. Nihayetinde bu çalışmada; 11 Eylül olaylarından bugüne, Avrupa’da yükselişe geçen İslam karşıtlığının geldiği yer ve gelişeceği yön üzerine bir analiz yapılmıştır. Özellikle son dönemlerde İsveç’te yaşanan olayların, siyasal ve teolojik boyutları anlaşılmaya çalışılmıştır. Akabinde yaşanan gelişmeler neticesinde, Avrupa’da yükselen İslam karşıtlığının İslam toplumlarında oluşturduğu etkiler analiz edilmiştir. En nihayetinde ise sorunun aşılabilmesi için gerekli olan siyasal, sosyolojik ve teolojik adımlardan bahsedilmiştir. Çalışma sürecinde literatür taraması yapılarak, bilimsel bir metot izlenmiştir.
11 EYLÜL’DEN BUGÜNE, AVRUPA’DA İSLAM KARŞITI HAREKETLER ÜZERİNE BİR ANALİZ: İSVEÇ ÖRNEĞİ
Keywords: Cultural Studies of Nation and Region; Ulus ve Bölgenin Kültürel Çalışmaları